Exploring Learning Styles in Students Attended Problem-Based Learning Package at Hue University of Medicine and Pharmacy - Nguyen Thi Anh Phuong; Trang Ho Thi Thuy; Ba Hai Mai; Duc Ton Nu Minh; Ha Hoang Thi Viet; Bao Ha Van Anh; Huy Nguyen Vu Quoc (Journal of Problem-Based Learning, 2018)
Purpose Learning style differs among students; 4 were identified by David A. Kolb (1984). Learning style identification plays a vital role in enhancing learning performance in response to choice of approaches to engaging students, particularly for Problem-based learning (PBL) methods used in Hue University of Medicine and Pharmacy. This research aimed to identify the learning styles of those students responding to PBL packages and investigate relationships between their learning styles and academic performance. Methods The cross-sectional study was conducted nursing students (N=135) who engaged with PBL packages in the subject Fundamental Nursing 3 in the second semester of the academic year 2016-2017. A questionnaire consisted of items on general characteristics, a learning style scale (Kolb LSI 3.1), and details around academic performance. Data were analyzed by using SPSS 22.0 program. Results The findings indicated that the diverging is the descriptor of the preferred learning style of 43.7% nursing students; 24.4% represented the converging style; the accommodating style accounted for 18.5% and assimilating style was 13.3%. Our study had not yet found the effect of learning methods on the academic performance of nursing students (toward Formative result: F=0.872, p=0.235; toward Summative result: F=1.116, p=0.345). Conclusion A majority of nursing students chose the diverging learning style over others but there was no significant difference between academic performance and learning styles. Therefore, teachers should be flexible and use different stimuli for learning in order to attempt to engage learners in stimuli for learning about different situations, irrespective of their preferred style for learning. It is important to provide optimal learning environments for most students.